PENGARUH TEMUAN AUDIT, OPINI AUDIT, DAN TRANSPARANSI TERHADAP TINGKAT INTEGRITAS: STUDI EMPIRIS PADA PEMERINTAH DAERAH DI PROVINSI BANTEN BERDASARKAN HASIL SURVEI PENILAIAN INTEGRITAS KPK - Vizka Verdani Sudarmadi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of audit findings, audit opinions, and transparency on the level of integrity in local governments in Banten Province. The population in this study consists of all local governments in Banten Province during the 2021–2024 period. The sampling method used is saturated sampling with a total of 32 observations. The data used are secondary data obtained from BPK audit reports, official local government websites, and the Corruption Eradication Commission’s Integrity Assessment Survey (SPI). The analytical method used in this study is multiple linear regression analysis. The results show that audit findings, audit opinions, and transparency do not have a significant effect on the integrity level of local governments in Banten Province. These findings indicate that the achievement of good audit opinions and the implementation of transparency have not fully reflected the integrity of local governments.